LncRNA MALAT1 promoted high glucose‐induced pyroptosis of renal tubular epithelial cell by sponging miR‐30c targeting for NLRP3. Issue 9 (11th May 2020) - Liu, Chan; Zhuo, Hui; Ye, Mu‐Yao; Huang, Gu‐Xiang; Fan, Min; Huang, Xian‐Zhe
Abstract: Diabetic nephropathy (DN), characterized by the chronic loss of kidney function during diabetes, is a long‐term kidney disease that affects millions of populations. However, the etiology of DN remains unclear. DN cell model was established by treating HK‐2 cells with high glucose (HG) in vitro. Expression of metastasis‐associated lung adenocarcinoma transcript‐1 (MALAT1), miR‐30c, nucleotide binding and oligomerization domain‐like receptor protein 3 (NLRP3), caspase‐1, IL‐1β, and IL‐18 in treated HK‐2 cells were tested by quantitative polymerase chain reaction. HK‐2 cell pyroptosis was assessed using flow cytometry analysis. Lactate dehydrogenase (LDH) activity was examined with a LDH assay kit. Correlation among MALAT1, miR‐30c, and NLRP3 was examined via dual‐luciferase reporter assay. Here, we revealed that MALAT1 was upregulated, but miR‐30c was downregulated in HG‐treated HK‐2 cells, leading to upregulation of NLRP3 expression and cell pyroptosis. Knockdown of MALAT1 or overexpression of miR‐30c protected HK‐2 cells from HG‐induced pyroptosis. Meanwhile, we found that MALAT1 promoted NLRP3 expression by sponging miR‐30c through dual‐luciferase reporter assay. Moreover, the co‐transfection of sh‐MALAT1 and miR‐30c inhibitor could reverse the protective effects of the sh‐MALAT1 on the HG‐induced pyroptosis. These results confirmed that MALAT1 regulated HK‐2 cell pyroptosis by inhibiting miR‐30c targeting for NLRP3, contributing to a better understanding of DN pathogenesis and help to find out the effective treatment for DN.